ANALYSIS OF FORMALIN AND MICROBIAL CONTENT IN TRADITIONAL AND VALUE-ADDED PROCESSED FISH PRODUCTS AT DUMAI CITY - Aulia Azka; Nirmala Efri Hasibuan; Putri Wening Ratrinia; Sumartini Sumartini; Shiffa Febyarandika; Shalichaty Shalichaty; Muh Suryono; Basri Basri (Berkala Perikanan Terubuk, 2022)
Dumai City is an area located in the coastal area. Processed fishery products are found in Dumai. Processed fishery products are suspected of containing formaldehyde and microbial contamination that can harm health. This study determines the content of formalin and microbes in traditional and value-added processed fishery products in Dumai City. Formaldehyde content was carried out qualitatively with the formaldehyde test kit MERCK and total microbes using the TPC method . The results showed that formalin was found in three samples of traditional and value-added processed fishery products in Dumai City, namely gulama salted fish, salted squid, and crab sticks. As many as 60% of the samples had total bacteria that exceeded the SNI standard, the total bacteria contained were 5.0 x 105 col/gr.